1993
DOI: 10.1002/hc.520040412
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiselenagermoles and spirobisbenzodiselenagermoles

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Recently, we have shown [1,2] that the complexes of zirconium bearing two selenium atoms are good precursors to various heterocyclic systems particularly those with elements of the column 14. In this case, the transition metal complexes act as a source of the o-dichalcogenobenzene ligand, but we have found that the method recommended by Rauchfuss [3] could also be favorably employed for this purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have shown [1,2] that the complexes of zirconium bearing two selenium atoms are good precursors to various heterocyclic systems particularly those with elements of the column 14. In this case, the transition metal complexes act as a source of the o-dichalcogenobenzene ligand, but we have found that the method recommended by Rauchfuss [3] could also be favorably employed for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Among the chalcogen-containing germanium representatives, some with the ligands o-dioxa-or o-dithiaphenylene [2] and o-diselenaphenylene [4] have been already described, but to the best of our knowledge nothing was published about complexes with germanium-tellurium bonds and only little is known for germanium complexes with two different germanium-chalcogen bonds. The few works in this area concern oxygen-sulfur, oxygen-selenium [5] or sulfur-selenium [6] linkages taking part in digermaniumcontaining complexes bridged by the chalcogen atoms.…”
Section: Introductionmentioning
confidence: 99%